Challenges in calculation of the gamma index in radiotherapy – Towards good practice. (April 2017) - Hussein, M.; Clark, C.H.; Nisbet, A.
Highlights: Topical review of the issues affecting gamma index computation. Demonstrates the factors affecting 2D and 3D gamma index computation using an independent software. Recommendations for good practice in the calculation and reporting of the gamma index. Abstract: The gamma index (γ) is one of the most commonly used metrics for the verification of complex modulated radiotherapy. The mathematical definition of the γ is computationally expensive and various techniques have been reported to speed up the calculation either by mathematically refining the γ or employing various computational techniques. These techniques can cause variation in output with different software implementations. The γ has traditionally been used to compare a 2D measured plane against a 2D or 3D dose distribution. Recently, software algorithm and hardware improvements have led to the possibility of using measured 2D data from commercial detector arrays to reconstruct a 3D-dose distribution and perform a volumetric comparison against the treatment planning system (TPS). A limitation in this approach is that commercial detector arrays have so far been limited by their spatial resolution which may affect the accuracy of the reconstructed 3D volume and subsequently the γ calculation. Additionally, 3D versus 3D γ comparison adds a layer of complication in the calculation of the γ given the increase in the number of calculation points and the result cannot be as easily interpreted in the same way as 2D comparison. This review summarises and highlights the computational challenges of the γ calculation and sheds light on some of these issues by means of a bespoke MATLAB software to demonstrate the impact of interpolation, γ search distance, resolution and 2D and 3D calculations. Finally, a recommendation is made on the minimum information that should be reported when publishing γ results.